Victorian women's fiction : marriage, freedom and the individual - Foster, Shirley (Routledge library editions. Women, feminism and literature, 2012)
Focusing on the ways in which female novelists have, in their creative work, challenged or scrutinised contemporary assumptions about their own sex, this book's critical interest in women's fiction shows how mid-nineteenth-century women writers confront the conflict between the pressures of matrimonial ideologies and the often more attractive alternative of single or professional life. In arguing that the tensions and dualities of their work represent the honest confrontation of their own ambivalence rather than attempted conformity to convention, it calls for a fresh look at patterns of imaginative representation in Victorian women's literature. Making extensive use of letters and non-fiction, this study relates the opinions expressed there to the themes and methods of the fictional narratives. The first chapter outlines the social and ideological framework within which the authors were writing; the subsequent five chapters deal with the individual novelists, Craik, Charlotte Bronté, Sewell, Gaskell, and Eliot, examining the works of each and also pointing to the similarities between them, thus suggesting a shared female 'voice'. Dealing with minor writers as well as better-known figures, it opens up new areas of critical investigation, claiming not only that many nineteenth-century female novelists have been undeservedly neglected but also that the major ones are further illuminated by being considered alongside their less familiar contemporaries.